Consumer Preference for the Chevon Sausage in Blind and Nonblind Sensory Evaluations: A Comparative Study. (29th July 2022) - Mazhangara, Irene Rumbidzai; Chivandi, Eliton; Jaja, Ishmael Festus
Abstract : There are strong perceptions regarding chevon consumption, with its strong aroma and smell and its stringiness and gaminess being chief among them. Processing chevon into by-products has resolved this negative perception associated with fresh chevon. A blind and nonblind comparative sensory evaluation was performed to investigate participant preference for the chevon sausage versus pork and beef sausages. The sausages were made from minced shoulder meat. After grilling the sausages, they were cut into 0.5 cm thick slices. There were 52 and 20 participants in the blind and nonblind sensory evaluations, respectively. Using a 9-point hedonic scale, the participants evaluated each sausage for its juiciness, flavor, tenderness, and overall satisfaction. During the blind sensory evaluation, the participants were also asked to identify one of the most distinct sausages since the identity of the sausages was not known. The results showed no significant differences (P > 0.05 ) in the preferences for any of the sausages during the blind sensory evaluation. The choice for the most distinct sausage showed that pork (57.69%), beef (32.69%), and chevon (9.62%) sausages were all recognized. In the nonblind sensory, knowledge of the identity of the sausage significantly (P < 0.05 ) influenced South African participants' liking of the chevon sausage, with pork and chevon being the most and least liked sausages, respectively.